Terapia cognitiva conductual en adultos con trastorno por déficit de atención e hiperactividad - Sotil Recavarren, Daniela Francesca (2024)
ADHD is a prevalent diagnosis in 3% to 4% of the adult population, which, if left untreated, can affect the personal, academic and work environment. However, currently the required importance is not given to the diagnosis and treatment of ADHD in adults, which leads to a series of consequences. The aim of the study is to identify the effectiveness of Cognitive Behavioral Therapy in the treatment of ADHD in adults. Therefore, a search was carried out following the PRISMA guidelines (Page et al., 2021) in the databases of ScienceDirect, Scopus, Taylor & Francis Online, APA and Sage Journals, of which 10 articles were selected based on the previously established inclusion and exclusion criteria. As a result, the majority of the studies analyzed reported CBT as an effective treatment for adults with ADHD, as well as other related variables, such as depressive symptoms, stress and anxiety. However, it was found that this is more effective when accompanied by pharmacological treatment, especially in the case of residual symptoms. Finally, as the main limitation, it was found that the number of articles that analyze the ADHD and CBT variables in the adult population is small.